A NEW SPECIES OF THE GENUS SIRTHENEA SPINOLA (HETEROPTERA : REDUVIIDAE : PEIRATINAE) - ., SUCHETA; CHOPRA, N. P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
A new species of the genus Sirthenea Spinola, from Haryana (India), is named, described and illustrated.